f ( x ) = cos 2 x cos 4 x cos 6 x cos 8 x cos 1 0 x
For f ( x ) as defined above, find the value of x → 0 lim 5 5 sin 2 x 1 − ( f ( x ) ) 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Chew-Seong Cheong I attempted using Taylor series but it does not produce same answer u being calculus expert, can u help explain why so thanks
Log in to reply
I tried that too but the ( f ( x ) ) 3 is very complicated and hence prone to mistakes.
Problem Loading...
Note Loading...
Set Loading...
L = x → 0 lim 5 5 sin 2 x 1 − ( f ( x ) ) 3 = x → 0 lim 1 1 0 sin x cos x − 3 ( f ( x ) ) 2 f ′ ( x ) = x → 0 lim − 5 5 sin ( 2 x ) 3 ( f ( x ) ) 2 k = 1 ∑ 5 cos ( 2 k x ) − 2 k sin ( 2 k x ) f ( x ) = x → 0 lim 5 5 sin ( 2 x ) 6 ( f ( x ) ) 3 k = 1 ∑ 5 cos ( 2 k x ) k sin ( 2 k x ) = x → 0 lim 5 5 sin ( 2 x ) 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) sin ( 2 x ) cos ( 2 ( k − 1 ) x ) + sin ( 2 ( k − 1 ) x ) cos ( 2 x ) ) = x → 0 lim 5 5 sin ( 2 x ) 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) sin ( 2 x ) cos ( 2 ( k − 1 ) x ) + ( sin ( 2 k x ) cos ( 2 x ) − sin ( 2 x ) cos ( 2 k x ) ) cos ( 2 x ) ) = x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) cos ( 2 ( k − 1 ) x ) + sin ( 2 x ) tan ( 2 k x ) cos 2 ( 2 x ) − cos ( 2 x ) ) = x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) cos ( 2 ( k − 1 ) x ) + sin ( 2 x ) tan ( 2 k x ) ( 1 − sin 2 ( 2 x ) ) − cos ( 2 x ) ) = x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) cos ( 2 ( k − 1 ) x ) + sin ( 2 x ) tan ( 2 k x ) − tan ( 2 k x ) sin ( 2 x ) − cos ( 2 x ) ) = x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( cos ( 2 k x ) cos ( 2 ( k − 1 ) x ) − tan ( 2 k x ) sin ( 2 x ) − cos ( 2 x ) ) + x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 sin ( 2 x ) k tan ( 2 k x ) = 5 5 6 k = 1 ∑ 5 k ( 1 − 0 − 1 ) + x → 0 lim 5 5 6 ( f ( x ) ) 3 k = 1 ∑ 5 k ( 2 cos ( 2 x ) 2 k sec 2 ( 2 k x ) ) = 0 + 5 5 6 k = 1 ∑ 5 k 2 = 5 5 6 × 6 5 ( 6 ) ( 1 1 ) = 6 A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x . Note that sin ( 2 k x ) = sin ( 2 x + 2 ( k − 1 ) x ) A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. x .